3‑Hydroxyquinazoline derivatives, analogues of erastin, induced ferroptosis in breast cancer cells Additional material - L. M. Borisova; V. N. Osipov; I. S. Golubeva; M. P. Kiseleva; D. A. Khochenkov; A. A. Vartanian (Успехи молекулярной онкологии)
.